Synthesis of Metakaolin Based Alkali Activated Materials as an Adsorbent at Different Na2SiO3/NaOH Ratios and Exposing Temperatures for Cu2+ Removal - Masdiyana, Ibrahim; Wan Mastura, Wan Ibrahim; Mohd Mustafa Al Bakri, Abdullah; Nabialek, Marcin; Putra Jaya, Ramadhansyah; Setkit, Monthian; Romisuhani, Ahmad; Je˙z, Bartłomiej (MDPI AG, Basel, Switzerland, 2023)
Water contamination is a major issue due to industrial releases of hazardous heavy metals. Copper ions are among the most dangerous heavy metals owing to their carcinogenicity and harmful effects on the environment and human health. Adsorption of copper ions using alkali activated materials synthesized through the polycondensation reaction of an alkali source and aluminosilicates is the most promising technique, and has a high adsorption capability owing to a large surface area and pore volume. This research focuses on the effect of the alkaline activator ratio, which is a sodium silicate to sodium hydroxide ratio. Various exposing temperatures on metakaolin based alkali activated materials on a surface structure with excellent functional properties can be used as adsorbent materials for the removal of copper ions. A variety of mix designs were created with varying sodium silicate to sodium hydroxide ratios, with a fixed sodium hydroxide molarity, metakaolin to alkali activator ratio, hydrogen peroxide, and surfactant content of 10 M, 0.8, 1.00 wt%, and 3.0 wt%, respectively. Most wastewater adsorbents need high sintering temperatures, requiring an energy-intensive and time-consuming manufacturing process. In this way, metakaolin-based alkali activated materials are adsorbent and may be produced easily by solidifying the sample at 60 °C without using much energy. The specific surface area, water absorption, microstructure, phase analysis, functional group analysis, and adsorption capability of copper ions by metakaolin based alkali activated materials as adsorbents were evaluated. The water absorption test on the samples revealed that the sodium silicate to sodium hydroxide 0.5 ratio had the highest water absorption percentage of 36.24%, superior pore size distribution, and homogeneous porosity at 60°C, with a surface area of 24.6076 m2/g and the highest copper ion uptake of 63.726 mg/g with 95.59% copper ion removal efficiency at adsorption condition of pH = 5, a dosage of 0.15 g, 100 mg/L of the initial copper solution, the temperature of 25 °C, and contact time of 60 min. It is concluded that self-supported metakaolin based alkali activated material adsorbents synthesized at low temperatures effectively remove copper ions in aqueous solutions, making them an excellent alternative for wastewater treatment applications.